A Thermochemical Heat Storage System for Households Combined Investigations of Thermal Transfers Coupled to Chemical Reactions - Fopah Lele, Armand (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2016)
The book offers a comprehensive report on the design and optimization of a thermochemical heat storage system for use in buildings. It combines theoretical and experimental work, with a special emphasis on model-based methods. It describes the numerical modeling of the heat exchanger, which allows recovery of about two thirds of the waste heat from both solar and thermal energy. The book also provides readers with a snapshot of current research on thermochemical storage systems, and an in-depth review of the most important concepts and methods in thermal management modeling. It represents a valuable resource for students, engineers and researchers interested in thermal energy storage processes, as well as for those dealing with modeling and 3D simulations in the field of energy and process engineering.